Uncovering the Filipino mothers’ experiences in teaching young children during uncertain times through reflexive thematic analysis - Arnilla, Arvin Kim; Casimero, Juvy Mariano; Biray, Ersyl Tatoy; Navejas, Amelia Tersol; Israel, Perlita Rodaste (Journal of Education and e-Learning Research, 2023)
The present study examined the preparations made by 14 mothers to ensure that their children’s education was unhampered during the COVID-19 crisis and ready for face-to-face classes when permitted. The study used a reflexive thematic analysis of the face-to-face interviews with participants belonging to low-income families living in the central Philippines whose children used printed modules as teaching materials provided by the school. The study generated three themes: “realizing the gaps” (realizing that in-person campus-based instruction is better because distant learning is not effective); “filling in the gaps” (taking the lead in teaching the child at home and assisted by family and community members) and “getting back on track” (preparing children for face-to-face classes against the COVID-19). The study showed how Filipino parents particularly mothers kept their children in school despite pandemic-induced uncertainties, economic scarcities and social inequalities. The desire driven by the perceived benefits derived from education brought out the pathways to resourcefulness. This study draws attention to equal opportunities for learning across socio-economic statuses and a more inclusive delivery of instruction during a crisis such as the COVID-19 pandemic.